Income, tax knowledge, and tax incentives impact on MSME tax compliance in COVID-19 - Ni Luh Putu Western Thelmalia; Gde Putra Pemayun; Caren Angellina Mimaki (Review of Management, Accounting, and Business Studies, 2023)
This study aimed to determine the effect of income level, tax knowledge, and the application of tax incentive policies partially on taxpayer compliance. The research method used was quantitative. The population in this study comprised taxpayers who had a business type of UMKM registered at KPP Pratama Gianyar, and the sample used consisted of 100 people. The data analysis techniques included the Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test, F Test, and t-test. From the results of the study, the following were obtained: (1) The level of income had a significant positive effect on taxpayer compliance, where the t-coefficient value was 3.598, the regression coefficient value was 0.364, and the significance was 0.001. (2) Tax knowledge had a significant positive effect on taxpayer compliance, with the t-coefficient value being 4.339, the regression coefficient value 0.335, and the significance 0.000. (3) The application of tax incentive policies had a significant positive effect on taxpayer compliance, with the t-coefficient value being 3.159, the regression coefficient value 0.210, and the significance 0.002. The suggestion in this study was that the Gianyar KPP Pratama should provide a tax burden that was in accordance with the taxpayer's business income and routinely provide tax socialization to increase taxpayer knowledge. Additionally, the Gianyar KPP Pratama should provide fair tax incentives to all taxpayers who meet the conditions for receiving them.